The Evolution of Islamic Philanthropy in Kampar Regency, Indonesia: A Historical Analysis from Traditional to Modern Practices - Bakar, Abu (Institut Agama Islam Negeri (IAIN) Manado, 2024)
This study examines the transformation of Islamic philanthropy in Kampar Regency, Indonesia, from traditional practices to modern approaches. Using a qualitative method with a historical case study design, the research explores the evolution of zakat, infaq, and sedekah practices from the Riau-Lingga Sultanate era through the Dutch colonial period, post-independence, and into the contemporary era. Data were collected through in-depth interviews with community leaders, philanthropic institution managers, and document analysis. The findings reveal that the transformation has been influenced by factors including globalization, increasing religious literacy, and technological advancements. The study highlights the shift from personal, community-based philanthropic practices to more institutionalized, professional approaches utilizing digital platforms. While this transformation has increased efficiency and social impact, challenges remain in maintaining Islamic values and local wisdom. The research also identifies disparities in the distribution of philanthropic benefits between Muslim majority and non-Muslim minority groups. This study contributes to the understanding of Islamic philanthropy's evolution in changing socio-cultural contexts and provides insights for developing more inclusive and sustainable philanthropic practices in diverse communities.